Redemption and reform in A Secular Age: Charles Taylor's interpretation of early modern Protestantism - Wallace, NJ (2023)
This dissertation presents a critical historiographical study of Charles Taylor’s A Secular Age (2007), focused on his interpretation of early modern Protestantism. Its biographical research together with intellectual-historical analysis of Taylor’s writings as a New Democratic Party politician and social theorist demonstrates that his “story” is intended to function as a Gramscian-Sorelian social myth to cultivate solidarity and subvert capitalist hegemony in the tradition of socialist humanism. The dissertation then explicates how that intention causes Taylor to misrepresent Protestant theology and experience. Its analytic foci include Taylor’s phenomenological argument that John Calvin disenchanted the Lord’s Supper, his reading of Richard Baxter’s political theology as a teleological retrojection of scientific socialism and Stalinism, and the liberal pluralist philosophy of religion inherent in his interpretation of Jonathan Edwards’s experience of redemption as a kind of “fullness”. The underpinnings of Taylor’s approach are clarified from his intellectual biography: his formative engagement with Catholic Personalism, Catholic Action, Cité Libre, the Canadian Social Gospel, the Student Christian Movement, and the “Canadian Fabians” while studying History at McGill University (1949–1952); alongside an examination of his role in the post-1956 formation of the British New Left at Oxford (1952–1961), observing his familiarity with the first English edition of Gramsci’s writings, his rediscovery of Marx’s 1844 manuscripts, and his appropriation of phenomenology from Merleau-Ponty. The dissertation critically elucidates how these sources (mis)guide his narrative construction by empirically falsifying Taylor’s presentation of an intrinsic causal link between Protestantism and secularization through e.g., examination of Calvin’s theology of the Supper with attention to his emphasis on the sacrality of the consecrated elements. The dissertation illustrates that an intrinsically theological, empirical ecclesiastical history committed to the ideal of historical writing as literary mimesis more accurately represents Christian experience by writing a history of redemption rather than Reform Master Narrative.